Analysis of Mathematically Creative Thinking Ability in View of Students’ Curiosity in E-module Assisted Creative Problem-Solving Learning (Universitas Negeri Semarang, 2022)
This study aims to describe the level of mathematical creative thinking ability in terms of students' curiosity. The research method used is a mixed method method with a sequential explanatory design. Quantitative data was obtained through pre-test and post-test, while qualitative data was obtained through questionnaires and interviews. The population in this study were all students of class VII SMP N 1 Sayung with a sample of two classes, namely, the control class and the experimental class taken by purposive sampling. The results showed that Creative Problem-Solving learning assisted by e-module was effective on students' mathematical creative thinking abilities. There is a significant influence of students' curiosity variables on the ability to think creatively mathematically. In the analysis of mathematical creative thinking ability, students with high curiosity master the four indicators of creative thinking ability, namely fluency, flexibility, originality, and elaboration. Students with curiosity are mastering the three indicators, namely fluency, flexibility, and originality. While students with low curiosity master two indicators, namely fluency and flexibility.